Política de drogas e garantismo: o caminho para a efetivação de um direito penal mínimo - Nottingham, Andrea de Boni (2017)
The world drug report, developed by the United Nations Office on Drug and Crime (UNODC), indicates that there are about 250,000,000 illicit drug users in the world. Of this amount, only 11.8% are problematic users, that is, people suffering from dependence or with some disorder derived from drug use. But given the way in which drugs are commonly handled by states, the minority of such people receive adequate health care, which demonstrates the need for a change of focus on the drug problem. In Brazil, the situation is even more critical, since while most countries have been breaking paradigms and reformulating their public policies on the subject, the country is still bound by highly repressive and ineffective legislation, which is no longer in line with the Democratic State of Law established by the Federal Constitution of 1988 and with the dictates therein laid down. Therefore, adopting Luigi Ferrajoli's Theory of Criminal Guaranteeism as a theoretical framework, the present work has the general objective of analyzing the inadequacy, in the face of the Federal Constitution, of the prohibitionist drug policy in Brazil. For this, the methodology is characterized as a qualitative approach, as it considers the existing theories about the theme, as well as the different perspectives to finally carry out a reflective work that can arrive at the expected and compatible result, both with the legal system, as well as with the factual reality. As for the source, the research is bibliographical and documentary, since it will use data already analyzed by the doctrine, as well as official documents, not yet interpreted. In relation to the objectives, it is exploratory, explanatory, and descriptive. Armed with this methodological support, it was possible to get to the result that prohibitionism has brought more harm than good, which is why it must be immediately rethought. In addition, it was clear that the Brazilian legal system is broadly compatible with Criminal Theory of Guaranteeism, another reason the current perspective of coping with drug policy must be changed. Lastly, in view of the pre-established premises, the possibility of adopting an effective harm reduction policy, appropriate to the factual reality, which may be more fruitful in relation to the drug problem than the one currently in force, is evident. main consequence, until the present moment, was the fortification of individual and institutional violence. Key words: Drug policy. Prohibitionism. Theory of Criminal Guaranteeism. Legal rights. Harm reduction.